AUTOGATE SYSTEM IMPLEMENTATION TO THE NUMBER OF CROSSING OF INDONESIA CITIZENS AT SOEKARNO-HATTA IMMIGRATION CHECKPOINTS - Samuel Budi Santoso (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
Judging from the number of crossings in the last three decades, the autogate system is still very far from being compared to manual counters. The public prefers manual counters as immigration checkpoints compared to the autogate facilities provided by the Directorate General of Immigration. In fact, if viewed from its implementation, autogate was built to speed up the immigration check process at the immigration checkpoint so that it can reduce frequent queues and improve the quality of public services. This autogate system should be the primary choice for the community to use it in the travel document inspection process. Therefore, the researcher wants to examine the implementation of the autogate system on the number of crossings of Indonesian citizens at TPI Soekarno-Hatta. The research method used in this research is descriptive qualitative. Collecting data using interviews, observation and documentation as well as supporting data for primary and secondary data. From this data, it can be processed to get a conclusion on the inhibiting factors of the number of autogate crossings for Indonesian citizens at Soekarno-Hatta Airport. The results of this research are academically beneficial to various parties while for immigration officials, it can be used as a reference in conducting further research for evaluation materials to improve all policies and maximizing the autogate system and also a reference for making other policies.